Effect of Glucagon-like Peptide-1 on High-Glucose-induced Oxidative Stress and Cell Apoptosis in Human Endothelial Cells and Its Underlying Mechanism. Issue 2 (August 2015) - Wang, Rehua; Lu, Lihong; Guo, Yansong; Lin, Feng; Chen, Haifeng; Chen, Wei; Chen, Minsheng
Abstract : Abstract: Glucagon-like peptide-1 (GLP-1) has been demonstrated to play an important role in type 2 diabetes mellitus, leading to cardiovascular diseases. This study aimed to examine the GLP-1 regulation of high-glucose-induced oxidative stress and cell apoptosis in human umbilical vein endothelial cells (HUVECs) and its underlying mechanism. HUVECs were isolated from healthy umbilical cords and cultured. GLP-1 and the GLP-1R antagonist, exendin (9–39), were used to pretreat the cells. The expression of NADPH oxidase subunits gp91 and p22 phox messenger RNA was detected by real-time quantitative polymerase chain reaction. Reactive oxygen species production was detected with flow cytometry and fluorescence microscopy. Lucigenin assay was used to measure the NADPH oxidase activity. The terminal deoxynucleotidyltransferase-mediated dUTP nick end labeling assay was used to investigate endothelial cell apoptosis. Apoptosis proteins were detected by immunoblotting. GLP-1 decreased high-glucose-induced oxidative stress, the expression of gp91 and p22phox messenger RNAs, and NADPH oxidase activation. Exendin (9–39) antagonized the effects of GLP-1 on high-glucose-induced oxidative stress. GLP-1 also increased HUVEC's high-glucose-induced proliferation and inhibited apoptosis. GLP-1 inhibited high-glucose-induced oxidative stress and cell apoptosis in HUVECs through GLP-1R–dependent and GLP-1 (9–36)–related pathways. GLP-1 suppressed high-glucose-induced oxidative stress and consequently may have an antiatherosclerosis effect on diabetes mellitus patients.